2016
DOI: 10.1136/gutjnl-2016-312712
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of screening colonoscopy in reducing the risk of death from right and left colon cancer: a large community-based study

Abstract: ObjectiveScreening colonoscopy's effectiveness in reducing colorectal cancer mortality risk in community populations is unclear, particularly for right-colon cancers, leading to recommendations against its use for screening in some countries. This study aimed to determine whether, among average-risk people, receipt of screening colonoscopy reduces the risk of dying from both right-colon and left-colon/rectal cancers.DesignWe conducted a nested case–control study with incidence-density matching in screening-eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
247
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 314 publications
(261 citation statements)
references
References 43 publications
7
247
0
7
Order By: Relevance
“…In addition, specialty guidelines recommended earlier or more frequent CRC screening for members of high-risk population groups-hereditary CRC syndromes, individuals with first-degree relatives with CRC, and patients suffering from inflammatory bowel disease [2][3][4][5]. Research has demonstrated that compared with no endoscopic screening, receipt of a screening colonoscopy is associated with a 67% reduction in the risk of death from any colorectal cancer [adjusted odds ratio (aOR) = 0.33, 95% confidence interval (CI) 0.21-0.52] [8]. By cancer location, screening colonoscopy is associated with a 65% reduction in risk of death for right colon cancers (aOR = 0.35, CI 0.18-0.65) and a 75% reduction for left colon/rectal cancers (aOR = 0.25, CI 0.12-0.53) [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, specialty guidelines recommended earlier or more frequent CRC screening for members of high-risk population groups-hereditary CRC syndromes, individuals with first-degree relatives with CRC, and patients suffering from inflammatory bowel disease [2][3][4][5]. Research has demonstrated that compared with no endoscopic screening, receipt of a screening colonoscopy is associated with a 67% reduction in the risk of death from any colorectal cancer [adjusted odds ratio (aOR) = 0.33, 95% confidence interval (CI) 0.21-0.52] [8]. By cancer location, screening colonoscopy is associated with a 65% reduction in risk of death for right colon cancers (aOR = 0.35, CI 0.18-0.65) and a 75% reduction for left colon/rectal cancers (aOR = 0.25, CI 0.12-0.53) [8].…”
mentioning
confidence: 99%
“…Research has demonstrated that compared with no endoscopic screening, receipt of a screening colonoscopy is associated with a 67% reduction in the risk of death from any colorectal cancer [adjusted odds ratio (aOR) = 0.33, 95% confidence interval (CI) 0.21-0.52] [8]. By cancer location, screening colonoscopy is associated with a 65% reduction in risk of death for right colon cancers (aOR = 0.35, CI 0.18-0.65) and a 75% reduction for left colon/rectal cancers (aOR = 0.25, CI 0.12-0.53) [8].…”
mentioning
confidence: 99%
“…Within the serrated class, hyperplastic polyps are not currently considered precancerous, whereas sessile serrated polyps (SSPs; also known as sessile serrated adenoma) and traditional serrated adenomas are considered precancerous ( should consider choosing colonoscopy. Although no randomized trials of colonoscopy for screening have been completed, extensive evidence from adenoma cohorts ( 30,31 ), cohort studies on incidence and mortality ( 55,56 ), and case-control studies (57)(58)(59)(60)(61)(62)(63)(64) support the effi cacy of colonoscopy in preventing incident CRC and cancer deaths. One cohort study ( 56 ) and 3 case-control studies ( 58,59,64 ) were performed in screening populations.…”
Section: Screening Targetsmentioning
confidence: 99%
“…Although no randomized trials of colonoscopy for screening have been completed, extensive evidence from adenoma cohorts ( 30,31 ), cohort studies on incidence and mortality ( 55,56 ), and case-control studies (57)(58)(59)(60)(61)(62)(63)(64) support the effi cacy of colonoscopy in preventing incident CRC and cancer deaths. One cohort study ( 56 ) and 3 case-control studies ( 58,59,64 ) were performed in screening populations. Reductions in incidence and mortality are approximately 80% in the distal colon and 40 to 60% in the proximal colon, at least in the United States and Germany ( 57,59,61,62,64 ).…”
Section: Screening Targetsmentioning
confidence: 99%
See 1 more Smart Citation